Analisis Kontruksi Sosial pada Puisi “Lelaki Tua pi Simpang Raya” Karya Raudah Jambak: Kajian Teori Peter L Berger & Thomas Luckmann - Chindy; Alysa Putri, Nasywa; Jelita Laoli, One Albert (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This research analyzes the poem "Lelaki Tua Di Simpang Raya" by Raudah Jambak through the social construction theory of Peter L. Berger and Thomas Luckmann, to understand how social reality is constructed through the experiences and interactions of individuals in society. This poem describes the social reality experienced by an old man as a result of social construction formed through interactions with others. This analysis highlights how the identity and meaning of an individual's life are formed through social processes involving externalization, objectivation, and internalization. The results show that social construction can influence and differentiate individuals in society, which invites readers to be more sensitive to social realities that are often ignored. This research uses a descriptive qualitative method to understand the relationship between literary works, social construction, and social reality.